2014
DOI: 10.1161/strokeaha.114.006600
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal Cell Transplantation Prevents Growth and Rupture in a Model of Rupture-Prone Saccular Aneurysms

Abstract: Background and Purpose-Aneurysm occlusion by intraluminal thrombus formation is the desired effect of all endovascular treatments. Intraluminal thrombus may, however, recanalize and be absorbed, unless it is infiltrated by cells that turn it into fibrous tissue (neointima). Because ruptured aneurysm walls are characterized by loss of smooth muscle cells, we assessed the impact of mural cell loss on wall remodeling of thrombosed aneurysms and investigated whether neointima formation could be enhanced by direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…Sodium dodecyl sulfate (SDS) is a detergent that destroys cells but leaves extracellular matrix intact. Its use for experimental decellularization worked well in a previously established rat model, where decellularized aneurysms have been shown to grow over time and eventually rupture, in contrast to aneurysms with vital vessel walls [6,9,11]. However, the completely decellularized graft (including eradication of endothelial cells) after SDS treatment may exhibit prothrombogenic properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium dodecyl sulfate (SDS) is a detergent that destroys cells but leaves extracellular matrix intact. Its use for experimental decellularization worked well in a previously established rat model, where decellularized aneurysms have been shown to grow over time and eventually rupture, in contrast to aneurysms with vital vessel walls [6,9,11]. However, the completely decellularized graft (including eradication of endothelial cells) after SDS treatment may exhibit prothrombogenic properties.…”
Section: Discussionmentioning
confidence: 99%
“…This process is mediated by smooth muscle cells and myofibroblasts, which migrate into the thrombus, presumably originating in the vessel wall. If there is a substantial diminution in the pool of these cells (i.e., after decellularization) the intraluminal thrombus will undergo cycles of lysis and re-thrombosis instead of scarification [6,11]. This instable thrombus formation causes local inflammatory reactions which promotes further vessel wall weakening.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, loss of mural cells and chronic aneurysm wall inflammation is a crucial factor for both saccular aneurysm growth and rupture. It has been demonstrated that aneurysms that lost mural cells also lost their ability to organize luminal thrombus and to form a neointima [8,33]. Instead, ongoing inflammation results in destructive wall remodeling, further mural cell loss and thinning of the vascular wall which in turn favors further aneurysm growth and rupture.…”
Section: Discussionmentioning
confidence: 99%
“…The small animal size and the intracranial aneurysms formed preclude the use of rodent CA models for endovascular device testing. To circumvent this issue, Frösen et al 21 and Marbacher et al 43 surgically created saccular aneurysms using a donor thoracic aorta, which was surgically ligated end-to-side to the abdominal aorta in both mice and rats. These saccular aneurysms display inflammatory cell infiltration, endothelial denudation, thrombus formation, and intimal hyperplasia.…”
Section: Surgically Created Saccular Aneurysmsmentioning
confidence: 99%